Finding the lost year : what happened when Little Rock closed its public schools? - Gordy, Sondra Hercher (University of Arkansas Press, 2009)
Sondra Gordy is professor of history at the University of Central Arkansas. She produced a documentary about the topic, entitled The Lost Year. A copy of the DVD can be ordered at www.thelostyear.com.